The use of a new chemical device based on silver and cationic surfactants as a new approach for daily oral hygiene: A preliminary study on a group of periodontal patients - Lauritano, Dorina (Int J Immunopathol Pharmacol, 2019)
The aim of this study was to evaluate the abatement power of oral microbial loading of a new gel formulation based on the complex silver-2-mercaptobenzoate, chlorhexidine digluconate and didecyldimethylammonium chloride (named ADC) through polymerase chain reaction (PCR). The study sample consists of a group of 20 patients with chronic periodontal disease. Patients were over 25 years of age and did not undergo surgical or non-surgical periodontal treatment in the previous 6 months. The study sample was allotted into two groups of 10 patients each, homogeneous by age and sex. The test group received a bottle containing ADC gel, while the control group received an identical one containing placebo, similar to ADC in consistence, colour, taste and odour. Sub-gingival samples of four sites, one in each quadrant, of greatest probing depth in each patient were used. Microbiological analyses were performed at baseline and at day 15. Paired t test was performed to detect statistical significant reduction in total bacterial loading and oral pathogens in the study groups. The analysis showed a statistically significant reduction in the total bacterial loading evaluated pre- and post-treatment (P = 0.029) in the study groups. In the control group, the decrease in total bacterial loading was not significant (P = 0.279). Clinically, ADC gel does not have any side effects and discomfort such as pain, burning, tingling sensation or numbness and produces no adverse reactions in time. Our study aimed to evaluate the efficacy of a new chemical formulation with antibacterial properties to use for daily oral hygiene with a preliminary study. Our results showed a statistically significant reduction in total bacterial loading after treatment, but the limitations of our study do not allow us to demonstrate the clinical efficacy of the ADC gel.